Local Chickens Farming System Characteristics and Their Genetic Resources Management in Seno Province of Burkina Faso - Ouédraogo, R. W.; Tindano, K.; Traoré, F. G.; Tapsoba, S. A. R.; Sanou, M.; Tamboura, H. H.; Bayala, B.; Traoré, A. (Tropical Animal Science Journal, 2023)
Local genetic resources have an important place in poultry production in Africa. However, knowledge of these genetic resources and their breeding systems is quite often limited. This study was carried out in Seno province/Burkina Faso and aimed to characterize the local chicken production system, the genetic resources used and their management in this area. A survey was conducted including 185 chicken farmers in a rural area. The snowball sampling method was used to co-opt interviewees and, face-to-face interviews were done. The questionnaire includes closed and open-ended questions. Production system characteristics showed that local chickens were bred in free-range production system with few inputs. There were multiple production purposes such as self-consumption (meat and eggs), saving, sale, making donation to strangers. The sale of chickens was ranked as the main purpose with 0.48 as the index, and self-consumption of chicken meat came in second position with 0.34 as the index. According farmers, three phenotypes of chickens ("breed or ecotypes") are encountered in the area. However, these phenotypes are raised together with uncontrolled mating practice, leading to a tendency towards uniformity of phenotypes. Almost all farmers (98.9%) stated they select breeding roosters. This selection is mainly based on growth performance (96.6%). Nevertheless, they ranked "resistance to diseases" as the characteristic they would improve primarily if they had all the possibilities (index 0.43). In general, the production system was extensive with low input, whereas the local chicken genetic resources were under poor management which can lead to genetic erosion.